How do UK banks react to changing central bank rates? - Fuertes, Ana Maria; Heffernan, Shelagh; Kalotychou, Elena (My University, 2010)
This paper explores the interest rate transmission mechanism using a broad disaggregated sample of UK deposit and credit products. For a large proportion of rates the adjustment speed is time-varying, switching among four regimes according to the direction of the policy rate and its effect on the disequilibrium gap. In general, this sign asymmetry implies faster adjustment to the long run path when the policy rate revision widens the gap. There is evidence of curvature in the catch-up effect towards equilibrium, namely, large gaps entail a disproportionately faster correction although mainly for deposits. The size of the policy rate change also impacts the adjustment speed. The notable heterogeneity found across financial institutions/products regarding the presence of these nonlinear patterns raises important questions on how to assess the effectiveness of monetary policy. The cross-section heterogeneity uncovered can be explained to some extent by diversification, profit volatility, product range, market concentration and menu costs.
Keywords: Adjustment speed; Curvature; Error correction model; Regime-switching; Time-variation